2020
DOI: 10.1016/s0140-6736(20)30214-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-lasting insecticidal nets with and without piperonyl butoxide on malaria indicators in Uganda (LLINEUP): a pragmatic, cluster-randomised trial embedded in a national LLIN distribution campaign

Abstract: Background Long-lasting insecticidal nets (LLINs) are the primary malaria prevention tool, but their effectiveness is threatened by pyrethroid resistance. We embedded a pragmatic cluster-randomised trial into Uganda's national LLIN campaign to compare conventional LLINs with those containing piperonyl butoxide (PBO), a synergist that can partially restore pyrethroid susceptibility in mosquito vectors.Methods 104 health sub-districts, from 48 districts in Uganda, were randomly assigned to LLINs with PBO (PermaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
164
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(174 citation statements)
references
References 29 publications
10
164
0
Order By: Relevance
“…Dual-active ITNs (pyrethroid plus piperonyl butoxide (PBO) or pyrethroid plus chlofenapyr) are now being deployed in the study area. PBO-pyrethroid ITNs have been shown to be more effective in reducing malaria than pyrethroid-only ITNs in areas of pyrethroid-resistant vectors [50,51], and monitoring of the effectiveness of these dual active ITNs is ongoing in Burkina Faso. Indoor residual spraying (IRS) should also be considered as it has been shown to be effective in reducing malaria in other high-burden countries.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-active ITNs (pyrethroid plus piperonyl butoxide (PBO) or pyrethroid plus chlofenapyr) are now being deployed in the study area. PBO-pyrethroid ITNs have been shown to be more effective in reducing malaria than pyrethroid-only ITNs in areas of pyrethroid-resistant vectors [50,51], and monitoring of the effectiveness of these dual active ITNs is ongoing in Burkina Faso. Indoor residual spraying (IRS) should also be considered as it has been shown to be effective in reducing malaria in other high-burden countries.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, another large-scale trial has been completed in 48 Ugandan districts with high pyrethroid resistance comparing PBO nets (i.e. Olyset Plus and PermaNet 3.0) with non-PBO nets (Olyset and PermaNet 2.0) [ 196 ]. The investigators measured malaria parasite prevalence among 2–10 year-olds, and demonstrated that any benefits accruable from the PBO nets over standard ITNs were marginal at 6 months (11% in PBO group versus 15% in non-PBO group), and null after 12 and 18 months.…”
Section: Could Itns With Multiple Active Ingredients Restore Insecticmentioning
confidence: 99%
“…The investigators measured malaria parasite prevalence among 2–10 year-olds, and demonstrated that any benefits accruable from the PBO nets over standard ITNs were marginal at 6 months (11% in PBO group versus 15% in non-PBO group), and null after 12 and 18 months. Surprisingly, the authors concluded, contrary to their own findings that the PBO nets were more effective, and even went further to suggest that their evidence should be adopted by the WHO to provide the “final” recommendation for PBO-Nets [ 196 ].…”
Section: Could Itns With Multiple Active Ingredients Restore Insecticmentioning
confidence: 99%
“…In a cluster randomized trial conducted in the same area as the present study, full coverage with PBO-Py ITNs (Olyset Plus) provided community protection against malaria up to 2 years of use (12). A further study, this one in Uganda, showed higher e cacy of PBO-Py ITNs compared to standard LLIN over the 18 months duration of the trial (13).…”
Section: Introductionmentioning
confidence: 54%